DESIGN APPLICATIONS BASED ON WEB MOBILE AT GAYA BARU SENIOR HIGH SCHOOL, CENTRAL LAMPUNG REGENCY AS PROMOTIONAL MEDIA - Ahmad Yudi; Bernadhita Herindri S. Utami; Rani Pratiwi (IJISCS (International Journal of Information System and Computer Science), 2017)
Gaya Baru Senior High School is one of the educational institutions in Lampung which is a less favorite institution in the area is precisely located in the district of Seputih Surabaya Central Lampung Regency. Gaya Baru Senior High School has already had a website but not many known. This Senior High School is also no information system through mobile web to promote the institution. Nevertheless, in its development, students or community want to find information about the school can be directly through the mobile web application. So in its development requires fast service. From research that conducted in Gaya Baru High School, existence of new mobile web application system will facilitate student or society of that area, especially in subdistrict Seputih Surabaya district Central Lampung, and present information about the info about situation in high school of new style it can be accessed directly through the mobile web media.